Neurotensin: A role in substance use disorder?. (February 2016) - Ferraro, Luca; Tiozzo Fasiolo, Laura; Beggiato, Sarah; Borelli, Andrea C; Pomierny-Chamiolo, Lucyna; Frankowska, Malgorzata; Antonelli, Tiziana; Tomasini, Maria C; Fuxe, Kjell; Filip, Malgorzata
Neurotensin is a tridecapeptide originally identified in extracts of bovine hypothalamus. This peptide has a close anatomical and functional relationship with the mesocorticolimbic and nigrostriatal dopamine system. Neural circuits containing neurotensin were originally proposed to play a role in the mechanism of action of antipsychotic agents. Additionally, neurotensin-containing pathways were demonstrated to mediate some of the rewarding and/or sensitizing properties of drugs of abuse. This review attempts to contribute to the understanding of the role of neurotensin and its receptors in drug abuse. In particular, we will summarize the potential relevance of neurotensin, its related compounds and neurotensin receptors in substance use disorders, with a focus on the preclinical research.